ENGLISH TRAINING AND LITERARY WORK CREATION FOR VOCATIONAL HIGH SCHOOL STUDENTS OF SMK NEGERI 1 SITUBONDO - Aziza, Aziza; Gibran, Rezal (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2024)
In the context of vocational education, equipping students with both English proficiency and creative expression skills is essential for enhancing their employability and personal development. This community-based project, conducted at SMK Negeri 1 Situbondo, Indonesia, aimed to strengthen students’ foundational English skills and promote creative literacy through a dual-focus approach: communicative English training and guided literary writing. Utilizing Communicative Language Teaching (CLT), Project-Based Learning (PjBL), and experiential learning frameworks, the program provided students with practical speaking exercises and mentorship in producing English-language poems and short stories. These works were curated and published in a collaboratively designed school wall magazine. The findings reveal that interactive instruction and creative output fostered student engagement, confidence, and linguistic competence. Moreover, the program functioned as a catalyst for promoting school-based literacy culture. This study highlights the pedagogical value of integrating language instruction with creative production in vocational settings and advocates for scalable, context-sensitive community engagement models to support English learning in under-resourced schools.